Primary Care - A brief summary that every Cephaliatrist should know - Ribeiro, Fernanda Cristina Poscai; Pereira, Kleber Fernando; César, Âlcantara Ramos de Assis (Headache Medicine, 2023)
Introduction Primary Health Care (PHC) serves as the foundation of the healthcare system, playing a vital role in disease prevention, treatment, and health promotion. It functions as the first point of contact between patients and the healthcare system, offering comprehensive and continuous care. Objectives The primary objective of this review is to provide an in-depth understanding of PHC, with a focus on its structure, processes, services, and projects, as a basis for potential initiatives related to headache disorders. Methodology The literature review encompassed various sources, including Google Scholar, Scielo, Pubmed/Medline, Lilacs, and government sources. Keywords related to PHC, including topics such as structure, functioning, and services, as well as specific areas like Women's Health, Mental Health, vaccination, and child healthcare, were employed. Results PHC is responsible for coordinating the Regionalized Healthcare Network (RAS), which includes Primary Care, communication centers, secondary and tertiary care points, support systems, and governance. PHC serves as the gateway, providing various services, including women's health, mental health, vaccination, child healthcare, and various other medical services. Furthermore, teams, such as the Family Health Strategy and the Family Health Support Center, play distinct roles in health promotion and care coordination. The focus of PHC includes territorialization, vaccination, wound care, women's health, and child healthcare, with a commitment to interventions and projects aimed at improving the quality of care and achieving positive outcomes. Conclusion PHC can play a crucial role in addressing headache disorders, offering early diagnosis, appropriate management, and the promotion of healthy habits. Investing in programs and professional training within PHC can be essential to provide effective care and reduce the demand for emergency care in cases of headache disorders.